Analisis Dampak Kebijakan Moneter Amerika Serikat terhadap Nilai Tukar Rupiah dan Inflasi Indonesia - Vivika, Amanda; Satria, Doni; Nelonda, Selli (Jurnal Kajian Ekonomi dan Pembangunan, 2025)
This study examines the impact of the United States Monetary Policy (FFR) on  Indonesia’s exchange rate and inflation , as well as how  Indonesia’s interest rate (SBI) responds to FFR changes using Vector Autoregression (VAR), Impulse Response Function (IRF), and Forecast Error Variance Decomposition (FEDV). The results indicate that FFR increases lead to Rupiah depreciation in the short term due to capital outflows, while inflation rises through cost-push inflation.  Although SBI is effective in stabilizing the exchange rate and inflation in the short term, its influence weakens over time as external factors become more dominant. Additionally, higher FFR reduces investment and consumption, which recover as domestic monetary policies stabilize. Thus,  Bank Indonesia must adjust interest rates, intervene in the foreign exchange market, and strengthen fiscal policy coordination to maintain economic stability amid global volatility.